2018
DOI: 10.1536/ihj.17-461
|View full text |Cite
|
Sign up to set email alerts
|

Aortic Dissection and Cardiac Dysfunction Emerged Coincidentally During the Long-Term Treatment with Angiogenesis Inhibitors for Metastatic Renal Cell Carcinoma

Abstract: Angiogenesis inhibitors, such as sorafenib and axitinib, which target vascular endothelial growth factor (VEGF) signaling, are widely used for renal cell carcinoma, including metastasis. In this study, we report a case of cardiovascular adverse events of aortic dissection and cardiac dysfunction during treatment with sorafenib and axitinib for metastatic renal cell carcinoma. A 66-year-old man had been administered sorafenib for 2 years after nephrectomy due to renal cell carcinoma. To control the progression … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
41
0
1

Year Published

2018
2018
2024
2024

Publication Types

Select...
8
1

Relationship

1
8

Authors

Journals

citations
Cited by 31 publications
(42 citation statements)
references
References 30 publications
0
41
0
1
Order By: Relevance
“…Long-term treatment with angiogenesis inhibitors for more than several years has been reported to cause aortic dissection. Adequate caution should thus be exercised with respect to cardiotoxicity affecting medium and large blood vessels 20 22 ) .…”
Section: Anti-angiogenetic Agents and Drug-induced Hypertensionmentioning
confidence: 99%
“…Long-term treatment with angiogenesis inhibitors for more than several years has been reported to cause aortic dissection. Adequate caution should thus be exercised with respect to cardiotoxicity affecting medium and large blood vessels 20 22 ) .…”
Section: Anti-angiogenetic Agents and Drug-induced Hypertensionmentioning
confidence: 99%
“…This is the first report on aortic dissection potentially related to the treatment of anlotinib in advanced lung cancer. Previous studies have also shown that anti‐angiogenic monoclonal antibodies and small‐molecule TKI can lead to aortic dissection (Table ).…”
Section: Discussionmentioning
confidence: 96%
“…VEGF is a leading regulator of angiogenesis. A large amount of evidence has demonstrated that the VEGF signaling pathway could directly promote blood vessel formation (32,33). Thus, the results indicated that DDAH1 contributes to exercise-induced cardiac angiogenesis.…”
Section: Discussionmentioning
confidence: 97%